Two-stage psychrophilic anaerobic digestion of food waste: Comparison to conventional single-stage mesophilic process - Rusín, Jiří; Chamrádová, Kateřina; Basinas, Panagiotis (Waste management (New York, N.Y.), 2021)
Food waste collected exclusively from University restaurant was tested under anaerobic digestion (AD) conditions to determine its biomethane generation potential. The digestion characteristics of food waste were evaluated in BMP tests and in a conventional single-stage mesophilic CST Reactor. The suitability of psychrophilic two-stage AD to convert food waste was investigated by using a novel two-stage psychrophilic semi-continuous reactor, consisted of a vertically-oriented cylindrical reactor and a coaxially incorporated vertical tube able to spatially separate acidification from methanogenesis. Food waste presented significant methane generation performance under mesophilic conditions. Relatively high amounts of H2S released during process evolution did not have a significant effect on biogas production. For psychrophilic two-stage AD, H2S generated during start-up provoked reactor's instability only for a few days. The system was stable and operated at steady-state conditions over the course of the main AD. Higher amount of biogas was produced by the two-stage psychrophilic reactor (0.800 m3 kgVS-1) than the mesophilic single-stage system (0.751 m3 kgVS-1). However, the average methane quantities generated by the two systems were remarkably similar (0.444 and 0.440 m3 kgVS-1). Psychrophilic process was more efficient in utilizing higher proportions of volatile organics contained in substrate for methane generation than mesophilic operation. The low-temperature two-stage reactor was more energy-efficient than the mesophilic CSTR for digestion of food waste. Two-stage anaerobic digestion system operating under psychrophilic conditions might be an economically feasible option for efficiently digesting food waste.
Keywords: Food; Refuse Disposal; BMP; Biofuels; odpadky - odstraňování; Methane; Bioreactors; Anaerobiosis; Psychrophilic digestion; Two-stage reactor; Anaerobic digestion; anaerobióza; Food waste; methan; Mesophilic digestion; biopaliva; bioreaktory; potraviny